2019
DOI: 10.17992/lbl.2019.09.247
|View full text |Cite
|
Sign up to set email alerts
|

Nárakviðslit - Yfirlitsgrein

Abstract: Nárahaular (groin hernia) eru algengust kviðslita og valda útbungun á nárasvaeði en geta auk þess valdið verkjum og jafnvel garnastíflu. 1,2 Aðgerðir á nárahaulum eru á meðal algengustu aðgerða í almennum skurðlaekningum 3 , en víða á Vesturlöndum eru framkvaemdar um 130-160 aðgerðir á 100.000 íbúa árlega. 4,5 Algengast er að aðgerð sé gerð vegna einkenna en einnig til að fyrirbyggja fylgikvilla, til daemis garnastíflu. Þetta er örugg aðgerð en helstu vandamálin eru endurtekin kviðslit og langvinnir verkir. 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 39 publications
0
7
0
14
Order By: Relevance
“…During the initial stages, PINK1 phosphorylates Ser65 of Ub (pSer65-Ub) to recruit autoinhibited cytosolic Parkin. [18][19][20] The pSer65-Ub-Parkin interaction stimulates Ub ligase activity, resulting in the formation of ubiquitin chains, which also serve as substrates of PINK1 to further retain and activate Parkin. Another consequence of the pSer65-Ub-Parkin interaction is that it releases the N-terminal Ub-like (Ubl) domain from the core of Parkin, increasing the rate at which PINK1 phosphorylates Ser65 of the Ubl domain.…”
Section: Introductionmentioning
confidence: 99%
“…During the initial stages, PINK1 phosphorylates Ser65 of Ub (pSer65-Ub) to recruit autoinhibited cytosolic Parkin. [18][19][20] The pSer65-Ub-Parkin interaction stimulates Ub ligase activity, resulting in the formation of ubiquitin chains, which also serve as substrates of PINK1 to further retain and activate Parkin. Another consequence of the pSer65-Ub-Parkin interaction is that it releases the N-terminal Ub-like (Ubl) domain from the core of Parkin, increasing the rate at which PINK1 phosphorylates Ser65 of the Ubl domain.…”
Section: Introductionmentioning
confidence: 99%
“…Complications of laparoscopic inguinal hernia repair include pain in the operative site and groin area, postoperative respiratory depression, postoperative nausea and vomiting after anesthesia, postoperative urinary retention, bladder injury, and scrotal hematoma, among which the scrotal or groin hematoma is the most common, with an incidence of 0.5% to 78%. [12] This study found that the incidence of respiratory depression and nausea and vomiting in patients after laparoscopic inguinal hernia repair was about 8%, and there was no statistical significance among all groups (P > .05), as shown in Table 5. In this study, a total of 1 case of surgical site hematoma occurred, and the patient was in group B.…”
Section: Adverse Eventsmentioning
confidence: 73%
“…Inguinal hernias are the most frequent type of hernia and their repair is among the most common procedures general surgeons perform. 1 Various risk factors can cause a predisposition to the development of hernias, such as male sex, old age, a high body mass index, connective tissue disorders and activity that increases intra-abdominal pressure, like chronic coughing or weight-lifting. 2 Inguinal hernias are divided into two categories depending on the point of protrusion of the tissue.…”
Section: Introductionmentioning
confidence: 99%